Effect of solution blown nanofibers on Mode-I fracture toughness and dynamic mechanical properties of carbon fiber-reinforced composites - EKİCİ, BÜLENT; POLAT, YUSUF (WILEY, 2021)
In this study, solution-blown nanofibers were coated on carbon fiber (CF) fabrics to improve Mode-I fracture toughness and dynamic mechanical properties of the composite laminates. Nanofiber coatings of various basis weights were directly spun over CF fabrics, which were then formed into composite laminates via vacuum-assisted resin transfer molding. A double cantilever beam test was conducted to analyze the Mode-I fracture toughness of CF-reinforced epoxy composites. The results showed that solution-blown nanofiber coatings stabilized the crack propagation and increased the delamination strength hence increased the Mode-I fracture toughness by nearly 48% for the addition of 1 g/m(2) nanofibrous web. Dynamic mechanical analysis was performed to investigate the effect of nanofibers on the stiffness of materials and the homogeneity of samples. Storage modulus, loss modulus, and damping factor were calculated, and corresponding Cole-Cole plots were drawn. DMA results showed that the stiffness of the composite sample increased up to 17% even after a minor amount (1 g/m(2)) of nanofiber coating.
Keywords: delamination; mode-I fracture toughness; nanofiber; polymer matrix composites; solution blowing method; ELECTROSPUN; MAT; THICKNESS; DAMAGE